2006
DOI: 10.1128/cvi.00199-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Enzyme Immunoassays for Detection of Immunoglobulin G Antibodies to Mumps Virus

Abstract: To determine suitability for national serosurveys, we compared two commercial enzyme-linked immunosorbent assays (ELISAs) for mumps antibody, Enzygnost Anti-Parotitis-Virus/IgG (which uses a whole-virus antigen) and Microimmune Mumps IgG Screen ELISA (which uses a recombinant nucleoprotein antigen), by testing 1,915 opportunistically collected sera submitted to diagnostic laboratories across Australia in 1997 to 1998. The proportion of positive results increased with age in both ELISAs but was significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Several reports have indicated that mumps-neutralizing antibody does not correlate particularly well with mumps IgG ELISA measurements (25)(26)(27)(28)(29)(30)(31)(32)(33). An explanation for these observations is that mumps antibodies predominantly measured by ELISAs which use whole-virus antigen differ from those measured by plaque neutralization tests.…”
Section: Mumps Igg Elisa Prn Titer Pre-and Post-mmr Vaccinationmentioning
confidence: 56%
See 2 more Smart Citations
“…Several reports have indicated that mumps-neutralizing antibody does not correlate particularly well with mumps IgG ELISA measurements (25)(26)(27)(28)(29)(30)(31)(32)(33). An explanation for these observations is that mumps antibodies predominantly measured by ELISAs which use whole-virus antigen differ from those measured by plaque neutralization tests.…”
Section: Mumps Igg Elisa Prn Titer Pre-and Post-mmr Vaccinationmentioning
confidence: 56%
“…Although neutralizing antibody is thought to be essential for protection (40) and PRN titration is generally considered to be the gold standard for mumps serology, previous attempts to determine a reliable threshold for protective PRN titers have been unsuccessful (20). To add further ambiguity, there have been several reports of poor correlations between mumps PRN titration and various other serologic methods, such as ELISA and immunofluorescent assays (IFA) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). These studies indicated that mumps serologic data must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,22 The limit of detection of the test was Ͻ230 of mumps IgG antibody titer. The cellular immune status to mumps vaccine was assessed by using an in vitro [ 3 H]thymidine incorporation assay as previously described.…”
Section: Study Patients and Immune Markersmentioning
confidence: 99%
“…Nucleoprotein antigen has been used to develop serological assays for a variety of paramyxoviruses and pneumoviruses; anti-N responses are routinely used to assess exposure to measles virus in epidemiological studies (12,(23)(24)(25)(26)(27). A side-by-side comparison of a human immunoglobulin RSV Lot 1 using the LIPS-N RSV and PRN tests over a wide range of IgG concentrations suggests that the LIPS-N RSV assay may also be more sensitive than the PRN assay in detecting RSV antibodies.…”
Section: Discussionmentioning
confidence: 99%